IMPLEMENTATION OF COMPENSATION POLICY AND STRENGTHENING EMPLOYEE COMPETENCY TOWARDS OPTIMIZATION OF EMPLOYEE JOB SATISFACTION - Maryani, Maryani; Nurhadi, Nurhadi; Ayob, Noorseha (Universitas Brawijaya, Indonesia, 2022)
The relationship of the variables in a study is the influence or relationship of these variables. This study aims to determine the effect of compensation and competence on job satisfaction, compensation on job satisfaction, and competence on job satisfaction. The independent variables are compensation and competence. The dependent variable is job satisfaction. The research was carried out at the Central Statistics Agency (BPS) Office of Makassar City, South Sulawesi, for approximately 2 (two) months, from May to July 2021. The population of this study was all employees who worked at the BPS Office, which was calculated for 82 people. The sampling technique was total sampling which involved all BPS employees. The type of data is primary data collected through a questionnaire. The results obtained that compensation and competence positively affect job satisfaction, compensation has a significant effect on job satisfaction, and competence has a positive but not significant effect on job satisfaction. Compensation and work competence at the Central Bureau of Statistics affects employee job satisfaction. That shows that compensation and competence are essential in employee job satisfaction. High job satisfaction can result in the company's performance going well.